Innovation: More than research and development. Growth opportunities on different innovation paths - Steffen Kinkel; Gunter Lay; Jürgen Wengel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2005)
On all levels of economy and society innovations are perceived as key success factor to economic growth and employment. Often it reads as follows: Increased research and development generates technologically innovative products, enabling companies to achieve competitive advantages and gain market shares, which eventually leads to economic growth and employment. This coherence has many times been empirically proven and was again confirmed by the Manufacturing Performance Survey 2003. At the same time the survey also revealed that other promising innovation strategies can be pursued: Companies that achieve innovative breakthroughs by intelligent product-service combinations or innovative techno-organisational processes also are superior to their competitors in regards to employment growth. This indicates that innovation can be more than just research and development. Innovative companies contributing to economic growth and employment can also be found in industrial sectors that are not as dedicated to research. They too ought to be appreciated and supported in their innovation efforts corre spondingly.
Keywords: 330